Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 14808 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Nerium oleander L." ] } The dataset includes 14808 records from 263 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0004863-150922153815467/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences